Menjembatani Teks dan Realitas: Tipologi dan Relevansi Asbāb al-Wurūd dalam Kajian Hadis Kontemporer di Indonesia - Putra, Aldo Marezka (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2022)
This article explores the epistemological and methodological development of asbāb al-wurūd as a pivotal framework in contemporary hadith interpretation. Recognizing the growing need for contextual reading of prophetic traditions, this study addresses the theoretical shifts from a normative-textual paradigm to a more interdisciplinary approach involving history, sociology, and anthropology. Using a qualitative library research method, the author examines seven scholarly articles published between 2011 and 2021 to map typologies, methodologies, and relevance of asbāb al-wurūd in Indonesia’s academic discourse. The findings reveal that contemporary scholars do not merely rely on transmitted reports (micro-level) but extend to macro-contextual analysis, interpreting hadith in light of socio-cultural and political realities of the Prophet’s era. Some scholars emphasize reinterpreting gendered or controversial traditions by employing social sciences to recover ethical meanings consistent with human dignity and justice. Others integrate asbāb al-wurūd into educational frameworks to foster critical thinking and spiritual awareness among students. Although variation in rigor and consistency among the articles is observed, the overall trend underscores the urgency of re-engaging hadith studies with contextual sensitivity. This article concludes that asbāb al-wurūd is no longer a mere explanatory tool but a dynamic hermeneutic method that bridges the gap between textual authority and the evolving realities of Muslim societies, thus reinforcing the living relevance of hadith in contemporary Islamic thought.